Kepemimpinan Transformasional, Budaya Organisasi, Dan Motivasi Kerja: Dampaknya Pada Kinerja Pegawai Sektor Publik - Nafiudin; Andari Andari; Anggit Yoebrilianti; Khadifa Puspa Ayu Pratiwi (Universitas Serang Raya, 2024)
This research aims to determine the influence of transformational leadership, organizational culture and work motivation on the performance of public sector employees. This research method uses quantitative methods with a population of 70 employees of the Serang Regency Communications, Informatics, Encryption and Statistics Service. The sampling technique in this research is a saturated sample. Saturated sampling is a sampling technique when all members of the population are sampled. The data sources obtained in this research were through observation, questionnaires and library research. Data analysis techniques were processed using the SPSS V.25 program. The results of this research were obtained using hypothesis testing which was carried out with a partial test (t test). The results show that, (1) transformational leadership has a positive and significant effect on employee performance. (2) Organizational culture has a significant negative effect on employee performance. (3) Work motivation has a positive and significant effect on employee performance